Transcriptome analysis reveals global gene expression changes of Chilo suppressalis in response to sublethal dose of chlorantraniliprole. (November 2019) - Meng, Xiangkun; Dong, Fan; Qian, Kun; Miao, Lijun; Yang, Xuemei; Ge, Huichen; Wu, Zhaolu; Wang, Jianjun
Abstract: The anthranilic diamide insecticide chlorantraniliprole was widely used for the controlling of Chilo suppressalis in China. Previous studies have revealed sublethal effects of chlorantraniliprole on the development and reproduction of C. suppressalis . In the present study, a comparative transcriptome analysis was performed to investigate the global gene expression changes in third-instar larvae of C. suppressalis after exposure to LC30 of chlorantraniliprole. A total of 908 differentially expressed genes (DEGs) were identified including 441 up-regulated and 467 down-regulated unigenes. Gene enrichment analysis revealed that the down-regulated DEGs were mainly linked to carbohydrate, energy, lipid and amino acid metabolisms as well as posttranslational modification, while most of the DEGs involved in signal transduction were up-regulated. Specifically, the DEGs encoding detoxification related genes were identified and validated by RT-qPCR. Our results provide a basis for understanding the molecular mechanisms of chlorantraniliprole action and detoxification in C. suppressalis and other insect pests. Graphical abstract: Image 1 Highlights: A comparative transcriptome analysis was performed in C. suppressalis after exposure to LC30 of chlorantraniliprole. The DEGs were significantly enriched in metabolisms, posttranslational modification and signal transduction mechanisms. The DEGs encoding detoxification related genes were identified and validated by RT-qPCR.